Unmanned aircraft systems traffic management : utm. - Baum, Michael S. (CRC Press, 2021)
This book introduces unmanned aircraft systems traffic management (UTM) and how this new paradigm in traffic management integrates unmanned aircraft operations into national airspace systems. Exploring how UTM is expected to operate, including possible architectures for UTM implementations, and UTM services, including flight planning, strategic coordination, and conformance monitoring, Unmanned Aircraft Systems Traffic Management: UTM considers the boundaries of UTM and how it is expected to interlace with tactical coordination systems to maintain airspace safety. The book also presents the work of the global ecosystem of players advancing UTM, including relevant standards development organizations (SDOs), and considers UTM governance paradigms and challenges. FEATURES Describes UTM concept of operations (ConOps) and global variations in architectures Explores envisioned UTM services, including flight planning, strategic coordination, conformance monitoring, contingency management, constraints and geo-awareness, and remote identification Highlights cybersecurity standards development and awareness Covers approaches to the approval, management, and oversight of UTM components and ecosystem Considers the future of UTM and potential barriers to its success, international coordination, and regulatory reform This book is an essential, in-depth, annotated resource for developers, unmanned aircraft system operators, pilots, policy makers, researchers, and academics engaged in unmanned systems, transportation management, and the future of aviation.